Blb-NRF2-PON1 Cross-Talk in Abdominal Aortic Aneurysm Progression - Magdalena P. Kasprzak; Bogna Gryszczyńska; Anna Olasińska-Wiśniewska; Tomasz Urbanowicz; Andrzej Jawień; Zbigniew Krasiński; Dorota Formanowicz (MDPI AG, 2023)
The progression of an abdominal aortic aneurysm (AAA) is an important issue, especially as AAA is becoming more common, and potentially life-threatening. This study aimed to understand better the mechanisms underlying AAA progression. For this purpose, we have focused on assessing the selected biomarkers whose potentially common denominator is the NRF2 (nuclear factor erythroid 2-related factor 2) transcription factor, that determines the selected antioxidant enzymes' activation. The study group consisted of 44 AAA male patients (71.41 ± 7.80 years aged). They were divided into three groups based on the aneurism diameter: group I (below 55 mm), group II (between 55 and 70 mm), and group III (over 70 mm). The laboratory analyses of PON1 (paraoxonase-1), NRF2, and HO-1 (heme oxygenase 1) were performed based on commercial ELISA tests; Blb (bilirubin) and hsCRP (high sensitivity C-reactive protein) were assessed during routine morphology examinations after admission to the hospital. Multiple linear regression showed that both bilirubin and NRF2 determined the PON1 concentration in the entire study group. The correlations between the examined parameters within the three studied groups suggest the capitulation of NRF2-dependent antioxidant mechanisms to pro-inflammatory processes. We showed that HO-1 and hsCRP may play a crucial role in the development of inflammation aneurism progression. Moreover, in patients with medium-sized aneurysms, antioxidant mechanisms were depressed, and inflammatory processes began to dominate, which may lead to uncontrolled growth aneurysm rupture. Our study is one of the first to indicate that the chronically activated antioxidant pathway using NRF2 may be a source of reduction stress.